Analisis Pengaruh Celebrity Endorser, Brand Image Dan Brand Trust Terhadap Keputusan Pembelian Shampoo Dove Di Semarang - M Roby Jatmiko (LPPM STIE Anindyaguna, 2021)
From the Top Brand Awards data, several shampoo brands from the Indonesia Best Brand Survey for shampoo products in Indonesia in 2019 - 2020 Dove Shampoo are at the bottom of the list. In 2019 the Top Brand Index (TBI) was 6.1% and in 2020 it showed an increase of 7.6%, but Dove shampoo was at the bottom and was not included in the TOP nominations. The population in this study were all consumers of Dove shampoo in Semarang with an unknown population. The number of samples was 96 people. The method of analysis using the SPSS program. The results show that celebrity endorsers have an effect on purchasing decisions, brand image has an effect on purchasing decisions, brand trust has an effect on purchasing decisions.